Influence of unique layered microstructure on fatigue properties of Ti-48Al-2Cr-2Nb alloys fabricated by electron beam melting. (April 2018) - Cho, Ken; Kobayashi, Ryota; Oh, Jong Yeong; Yasuda, Hiroyuki Y.; Todai, Mitsuharu; Nakano, Takayoshi; Ikeda, Ayako; Ueda, Minoru; Takeyama, Masao
Abstract: The influence of a unique layered microstructure consisting of duplex-like region and equiaxed γ grain layers (γ bands) on the fatigue properties of Ti-48Al-2Cr-2Nb alloy bars fabricated by electron beam melting (EBM) was investigated at room temperature (RT) and 1023 K focusing on the angle ( θ ) between the building direction and cylinder (loading) axis. We found for the first time the fatigue strengths of the alloy bars with the layered microstructure depend strongly on the angle θ . Particularly, the fatigue strength of the alloy bars fabricated at θ = 45° is comparable to that of the hot isostatic pressing (HIP) treated cast alloys, even without HIP treatment. We also found the alloy bars fabricated at θ = 0° and 45° exhibit high fatigue strengths in the low-cycle fatigue life region at 1023 K similar to θ = 45° alloy bars at RT. These high fatigue strengths are caused by inhibition of the brittle main crack initiation by stress relaxation due to shear deformation at the γ bands and large plasticity of the alloys. These findings indicate that the alloys fabricated by EBM at θ = 45° with the unique layered microstructure have a great potential for aerospace and automobile applications. Graphical abstract: Image 1 Highlights: The alloys with a layered microstructure show high fatigue strengths even without HIP. The fatigue behavior at room temperature depends on the layered microstructure. The fatigue behavior at 1023 K can be classified into two regions. Crack initiation is inhibited by stress relaxation at γ grain layers.